A study of fetomaternal outcome in elderly primigravida - Bhankhar, Ronak R.; Chavda, Anjali R.; Patel, Hemali N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Elderly primigravida is defined as all women going through their first pregnancy over the age of ≥35 years. They are considered to be categorized as high-risk pregnancy. Advanced contraception methods and artificial reproductive technology have played key role in delaying the pregnancy. Methods: A retrospective study of fetomaternal outcome in elderly primigravida was conducted at department of obstetrics and gynecology, GMERS medical college, Junagadh from 1st September 2021 to 1st August 2022. All the patient data was obtained from their case records and indoor files and were followed up till delivery for fetal outcome. Results: There were 54 elderly primigravida patients in our study with an incidence of 1.05% based on the inclusion criteria with 96.3% between the age 35-40 years. Most common reason for delayed child bearing was pursuing higher education and work preferences. Gestational hypertension was most common maternal complication (48%), associated with preeclampsia in 28%. Among fetal complications 46% had low birth weight, 38.5% had IUGR. 54% patients had delivered by LSCS. Conclusions: Although elderly primigravida is considered a high-risk pregnancy with increased maternal and fetal complications, proper antenatal care, early recognition of maternal risk factors with timely intervention pregnancy outcome can be improved.